Sandalwood (Santalum album Linn) development strategy to improve the economics society in Timor-Leste: community views - Adelino Rojario; Omo Rusdiana; Iin Ichwandi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Sandalwood (Santalum album Linn) is an endemic plant of TimorLeste that has high economic value and needs to be developed to achieve prosper society and the country. This research aims to discover people'sperceptions of sandalwood development in Timor-Leste. Data is obtained using questionnaires, surveys, observations, and documentation. The population from this study is 84 respondents consisting of 15% of the family head in both villages Maudemo and Aidabaleten based on the agricultural census 2019. Data was collected using a 15% sample. Data are analyzed descriptively with statistical percentage techniques with every possibility of the answers obtained from sharing the frequency received by the number ofsamples multiplied by 100%. The results showed that 100% of the community knew sandalwood well and its economic value. Many people have not planted and adopted government programs to grow sandalwood, community 8% have land above 1 hectare. The community 100% and 98% in both villages knowthat the government has conducted a planting program. The public has not adopted government programs, with respondents 88% in the village of Maudemo and 36% in the village of Aidabaleten. The community does not have business capital, so it needs seedling subsidies with respondents 100% and 69%, incentives 100% and 95%, and bank credit 100% and 88% in both villages. Massive sandalwood development requires government policies to socialize programs, laws, and regulations on sandalwood development. Therefore, a policy from the government is required to provide seedlings, incentives, and bank credit to the community.